2008
DOI: 10.2135/cropsci2008.01.0010
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Selection to Alter Grain Methionine Concentration and Improve Nutritional Value of Maize

Abstract: Methionine is an essential amino acid that is limiting in maize-(Zea mays L.) based diets. The objective of this work was to determine whether we could alter grain methionine concentration in random-mated maize populations by mass selection for methionine concentration using a microbial assay. In one study, we developed two populations by selecting for high or low methionine concentration (HM or LM, respectively) for three generations starting from the randommated population BS11. Grain from these populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 10 publications
(12 reference statements)
1
36
2
Order By: Relevance
“…While the effectiveness of dzr1 and recurrent selection were shown by Olsen et al (2003) and Scott et al (2008), respectively, the present study suggests there may be a benefit of having either or both methods in hybrid combination. Current data suggests synergism may exist between dzr1 and recurrent selection because of the significant SCA for methionine concentration in the RS3/B101 hybrid.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…While the effectiveness of dzr1 and recurrent selection were shown by Olsen et al (2003) and Scott et al (2008), respectively, the present study suggests there may be a benefit of having either or both methods in hybrid combination. Current data suggests synergism may exist between dzr1 and recurrent selection because of the significant SCA for methionine concentration in the RS3/B101 hybrid.…”
Section: Discussioncontrasting
confidence: 50%
“…One possible explanation for this observation is that the method used to quantify amino acids is not accurate. It has been shown that there is a high correlation between the AOAC standard method (AOAC International, 1995) for methionine analysis and the bacterial assay used in this study (Scott et al, 2008). In addition, it has been shown that selection for methionine using the microbial growth method results in populations with altered methionine concentration as measured by the AOAC standard high-performance-liquid-chromatograph-based method (Newell et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recurrent selection is one of the most simple ways to improve a trait, if there is a straightforward way to quantify the trait of interest and a population with heritable variation for the trait [7]. Recurrent selection is simply the selection for a certain trait or traits over many generations, and can be used to control complex multigenic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al recently examined the effects on the serum TRP ratio, brain TRP concentrations and 5HT synthesis of feeding groups of rats meals containing each of several proteins (zein, gluten, casein, soy, lactalbumin) [3]. The amino acid patterns of these proteins, notably their contents of TRP in relation to the other LNAA (i.e., the TRP ratios of the dietary proteins), range widely: lactalbumin, 0.048; soy protein, 0.033, gluten, 0.029, casein, 0.026 and zein, 0.015 [4][5][6]. At moderate levels in the diet, based on recent work by others [7,8], we wondered if the ingestion of these proteins might modify the serum TRP ratio in a direction reflecting their TRP ratios.…”
Section: Introductionmentioning
confidence: 99%